PENERAPAN MODEL PBL (PROBLEM BASED LEARNING) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI PECAHAN PADA SISWA KELAS V UPTD SD INPRES BAKUNASE 2 - Taek, Julita Reginaldis; Ekowati, Ch. Krisnandari; Benu, Adam B.N. (SINERGI : Jurnal Riset Ilmiah, 2025)
The Implementation of the PBL (Problem-Based Learning) Model to Improve Mathematics Learning Outcomes on Fraction Material The research problem is: How can the implementation of the PBL (Problem-Based Learning) learning model improve learning outcomes in fraction material for fifth-grade students at UPTD SD Inpres Bakunase 2 The aim of the study is to improve students' learning outcomes in fraction material by using the PBL (Problem-Based Learning) model for fifth-grade students at UPTD SD Inpres Bakunase 2.The research subjects consisted of 14 students, including 6 male and 8 female students.  The research method used was qualitative descriptive in the form of classroom action research (CAR), with data collection techniques including observation, tests, and document studies. The collected data were processed and further analyzed using qualitative descriptive analysis techniques. The results of the study in Cycle I showed that out of 14 research subjects, only 6 students (42.85%) achieved mastery, while the remaining 8 students (57.14%) did not meet the criteria. This was due to the teacher's lack of guidance during group tasks, students' low conceptual understanding of the material, and students not paying attention to the teacher's explanation when using teaching aids.In Cycle II, there was an improvement, as evidenced by 12 out of 14 students (85.7%) achieving mastery. This increase was due to the teacher's better classroom management and individual guidance during group tasks, improved student understanding of the material, and an increase in students' motivation to participate in learning and pay attention to the teacher's explanations